2018
DOI: 10.1109/tro.2017.2765335
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Deformations From Physical Human–Robot Interaction

Abstract: Abstract-Robots are finding new applications where physical interaction with a human is necessary: manufacturing, healthcare, and social tasks. Accordingly, the field of physical humanrobot interaction (pHRI) has leveraged impedance control approaches, which support compliant interactions between human and robot. However, a limitation of traditional impedance control is that-despite provisions for the human to modify the robot's current trajectory-the human cannot affect the robot's future desired trajectory t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 41 publications
(118 reference statements)
1
74
0
Order By: Relevance
“…It is this explicit estimation lens that exposes our choices for how to interpret and extrapolate from corrections, challenging or validating assumptions we've made in the past. From the perspective of work that uses non-Euclidean norms to deform trajectories [2], [16], we validate that these are also useful when learning cost functions based on the deformed trajectories. From the perspective of work that learns cost functions [1], [3], we challenge the notion that Euclidean norms are always best [3], and support the choice to sometimes use non-Euclidean deformation [1].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is this explicit estimation lens that exposes our choices for how to interpret and extrapolate from corrections, challenging or validating assumptions we've made in the past. From the perspective of work that uses non-Euclidean norms to deform trajectories [2], [16], we validate that these are also useful when learning cost functions based on the deformed trajectories. From the perspective of work that learns cost functions [1], [3], we challenge the notion that Euclidean norms are always best [3], and support the choice to sometimes use non-Euclidean deformation [1].…”
Section: Introductionmentioning
confidence: 69%
“…This has an intuitive interpretation: the robot uses the inverse of the norm to propagate the correction to the rest of the trajectory, while keeping the start and the goal fixed. This is analogous to using a norm to respond to changes in the goal, as in [2], and similar to work in responding to a force during haptic robot teleoperation [16] (there, the propagation happens not from the current point, but from a future time point, so that the human does not have to keep providing input).q…”
Section: B Formalism Of Intended Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar work on physically interactive trajectory deformations used an analytical smooth family of trajectories to find the local spatial deformations as a function of the applied force [16]. The analytical formulation allowed to use gradient-based optimization to find the parameters of the deformed trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [9] use affine transformations on parts of the motion trajectory which ensures preserving affine-invariant features of the original trajectory like line smoothness and velocity. More recently, the authors of [10] demonstrated optimal trajectory deformation through constrained optimization of an energy function ensuring the minimum-jerk profile. Although the resulting deformed trajectories are optimal, a main limitation in the above works is that the speed of the task is unchanged.…”
Section: Introductionmentioning
confidence: 99%